2021
DOI: 10.3892/ijmm.2021.4994
|View full text |Cite
|
Sign up to set email alerts
|

Sinigrin attenuates angiotensin II‑induced kidney injury by inactivating nuclear factor‑κB and extracellular signal‑regulated kinase signaling in vivo and in vitro

Abstract: The present study investigated the function of sinigrin in angiotensin II (Ang II)-induced renal damage. The results demonstrated that systolic blood pressure (SBP) and diastolic blood pressure (dBP) were increased in Ang II-challenged rats, and sinigrin treatment inhibited their increase. The levels of blood urea nitrogen (BUN) and serum creatinine (ScR) were increased by Ang II in the rats, and these were reversed by sinigrin in a dose-dependent manner. In addition, the Ang II-induced elevation of urinary pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…29,30 Although the complex relationship hypertension and renal dysfunction is still under debate, kidney damage is certainly a crucial complication of hypertension, accompanied by a severe inflammatory response, oxidative stress, kidney hypertropia, extracellular matrix accumulation, etc. 11 Mechanistically, various cytokines such as angiotensin II (Ang II) from the excessive active renin-angiotensin system (RAS) should be considered the culprit of hypertensive kidney damage. 28 Soybean-derived hydrolysates were demon-strated to attenuate blood pressure by mediating the serum exosome-derived miRNA-19b/CYLD/TRAF6 axis in the vascular microenvironment of SHRs in our previous study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30 Although the complex relationship hypertension and renal dysfunction is still under debate, kidney damage is certainly a crucial complication of hypertension, accompanied by a severe inflammatory response, oxidative stress, kidney hypertropia, extracellular matrix accumulation, etc. 11 Mechanistically, various cytokines such as angiotensin II (Ang II) from the excessive active renin-angiotensin system (RAS) should be considered the culprit of hypertensive kidney damage. 28 Soybean-derived hydrolysates were demon-strated to attenuate blood pressure by mediating the serum exosome-derived miRNA-19b/CYLD/TRAF6 axis in the vascular microenvironment of SHRs in our previous study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the function of sinigrin in Ang II-induced renal damage indicated that the levels of serum BUN and creatinine increased by Ang II in rats, which were reversed by sinigrin in a dose-dependent manner. 11 Mechanistically, sinigrin attenuated the Ang II-induced kidney damage by mediating oxidative stress and inflammation in the rats, which was related to the ERK and NF-κB signaling pathways. Hence, we further analyzed the renal pathology, inflammation factors (including IL-1β, IL-6, and TNF-α), and redox reaction in the WKY and SHR groups.…”
Section: Food and Function Papermentioning
confidence: 97%
See 1 more Smart Citation
“…[35,36,40] Folkloric literature and some published studies also demonstrate the antinociceptive and analgesic potential of the members of the Brassicaceae family. [26,[29][30][31]41] Although B. campestris is widely utilized in folk medicine all over the world, the antinociceptive effects of this plant have not yet been fully elucidated. The studies of plant species that are conventionally used for the relief of pain are still elusive and used as logical research strategies to investigate novel analgesic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…[28] Several studies conducted to characterize the pharmacological activities of sinigrin have demonstrated its potential anti-cancer, antibacterial, antifungal, antioxidant, anti-inflammatory, wound healing, and bio fumigation properties. [29][30][31] Brassica juncea, (also known as Indian mustard), is enriched in redox-active polyphenols with antidiabetic activities. [32][33] A study was conducted to determine the antinociceptive and anti-hyperglycemic potential of methanol extract of Brassica juncea in Swiss albino mice.…”
Section: Introductionmentioning
confidence: 99%